Transscleral diode laser retinopexy in retinal reattachment surgery - Goncalves, Joao Carlos de Miranda [UNIFESP] (2004)
PURPOSE: Transscleral diode retinal photocoagulation (diopexy) is becoming an accepted technique in the treatment of selected retinal diseases. The objective of this study is to evaluate diopexy technique in the production of adhesive chorioretinal lesions during the surgical treatment of the rhegmatogenous retinal detachment. METHODS: 25 patients with rhegmatogenous retinal detachment were enrolled in a prospective clinical-surgical study to evaluate the technique of transscleral diode laser photocoagulation to obtain adhesive chorioretinal lesions during retinal reattachment surgery. The surgery consisted of the placement of an exoplant silicon to produce a buckle effect combined with a drainage of subretinal fluid in most cases. RESULTS: By a mean follow-up of 10 months, 21 of 25 eyes had their retinas reattached after only one surgery with diopexy used in all cases. CONCLUSION: Transscleral diode laser photocoagulation was a technically easy, controlled, effective, reproducible and safe means of obtaining chorioretinal adhesion in retinal reattachment surgery.